FORMULASI DAN PEMBUATAN PAKAN PUYUH MENUJU KEMANDIRIAN PETERNAK DI DESA SUMBERINGIN KECAMATAN SANANKULON KABUPATEN BLITAR - Wardah Wardah; Tatang Sopandi (JPM17: Jurnal Pengabdian Masyarakat, 2015)
Sumberingin village, district of Sanankulon,  Blitar city, East Java is one of the village that became center of poultry farms. This potential large farm was driving to the emergence of  trade syndicate system of feed manufacturers, so it's easy playing the price and availability of animal feed. Beside that the spreading of  low-quality animal feed was also being a potential problem. These conditions caused the farmers of suffering  loss and even getting out of business. An  observation indicated that the local area is a producer of potential animal feed raw materials such as tubers, legumes, tofu, soybean, molasses and bekicot/snails. Formulation science and technology of high quality animal food is needed by the farmers and it is a form of technology transfer to farmers group "Mandiri" in Sumberingin village, Sanankulon, Blitar. The availability of mechanical machines in the form of dishmill production machine, mixer, mold and dryer are beneficial to farmers. These machines can increase productivity as well as quality of their products. In addition it is also expected to decresase the quail mortality rate due to new feed formulation. It can raise the quail immunity exposure to stress and disease. Various species of medicinal plants, especially pike (Phyllantusbuxifolius), known to be iimmuno stimulant are widely available in the local village. They are easily planted and cultivated so that the transfer of science and technology of medicinal plants can be beneficially conducted. The outcomes of this program include: (1) the product of nutrient animal feed is available as needed, relatively inexpensive, can improve the quail immunity and can be produced on an ongoing basis by independent farmers. (2) an ergonomic feed production machine, relatively inexpensive, functional, appropriate and easy to operate can be owned by farmers to produce functional animal feed for the quails. Keywords: animal feed formulation, quail, farmers